Former Terrorism Convicts and Politics of Citizenship (A Study About The Struggle of Former Terrorism Convicts To Receives Cultural Recognition From The Community in Bandar Lampung City) - Gede Ari Pratama Putra; R. Pitojo Budiono (Universitas Medan Area, 2023)
Terrorism is a transnational crime that endangers state ideology, state security, human values, and various aspects of social life. The fight against terrorism and the punishment of terrorist group members are carried out with special handling, including the handling of former terrorism convicts who have finished serving their prison sentences but may re-join terrorist organizations. Research on former terrorism convicts so far tends to be related to deradicalization efforts and patterns, therefore this qualitative research through in-depth interviews aims to describe the perspectives of former terrorism convicts in Bandar Lampung City regarding post-free dynamics and return to society. The research results were analyzed using Citizenship Theory and the dimensions of citizenship by Stokke (2017). As a result, former terrorism convicts have to experience cultural exclusion (membership dimension) and are faced with political recognition efforts (citizenship as members) and, at the end, they have to institutionalize their group in the form of an organization or foundation as a tool to gain cultural recognition from the community.